Efficacy of Cognitive Behavioral Therapy for Insomnia in Older Adults With Occult Sleep-Disordered Breathing. Issue 5 (June 2016) - Fung, Constance H.; Martin, Jennifer L.; Josephson, Karen; Fiorentino, Lavinia; Dzierzewski, Joseph M.; Jouldjian, Stella; Tapia, Juan Carlos Rodriguez; Mitchell, Michael N.; Alessi, Cathy
ABSTRACT: Objectives: The aims of the study were to determine whether mild, occult sleep-disordered breathing (SDB) moderates the efficacy of cognitive behavioral therapy for insomnia (CBTI) in older adults and to explore whether CBTI reduces the number of patients eligible for positive airway pressure (PAP) therapy. Methods: Data were analyzed for 134 adults 60 years or older with insomnia and apnea-hypopnea index (AHI) of less than 15 who were randomized to a larger study of CBTI versus a sleep education control. Sleep outcomes (sleep onset latency, total wake time, wake after sleep onset, sleep efficiency, Pittsburgh Sleep Quality Index) were compared between CBTI and control at 6 months using repeated-measures analysis of variance adjusted for baseline values. AHI of 5 or greater versus less than 5 was included as an interaction term to evaluate changes in sleep outcomes. The number of participants at baseline and 6 months with mild SDB for whom insomnia was their only other indication for PAP was also compared between CBTI and control. Results: AHI status (AHI ≥ 5 [75.5% of participants] versus AHI < 5) did not moderate improvements in sleep associated with CBTI (all p values ≥ .12). Nine (45.0%) of 20 participants with mild SDB for whom insomnia was their only other indication for PAP therapy at baseline no longer had another indication for PAP at 6 months, with no significant difference between CBTI and control. Conclusions: CBTI improves sleep in older veterans with insomnia and untreated mild SDB. Larger trials are needed to assess whether CBTI reduces the number of patients with mild SDB eligible for PAP. Abstract : Supplemental digital content is available in the text.